Ataques de onça-parda sobre criações domésticas no oeste do Estado de São Paulo - Fuini, Gabriela Rigotti [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The conflict between humans and wild carnivores due the predation on domestic livestock has been a reason that made the Carnivora one of the groups with most threatened species. In Brazil, predation by pumas has been recorded in various regions and result in a harsh persecution on these animals. In order to identify factors that might be associated with predation on domestic livestock by pumas in the west of São Paulo, we did interviews with farm owners and their regular employees using a semi structured questionnaire, addressing characteristics of the property, the management and landscape. We conducted 71 interviews and identified properties that had gone through predation events in the last decade. Sheep and cattle were the most often attacked species. Using logistic regression it was possible to obtain a predictive model of attacks with 81% agreement between estimated and observed, in which the number of sheep and amount of natural vegetation present in each property was positively related to cases of predation. However, a proper management of individuals under risk for both sheep and calves showed to be effective and can contribute significantly to reduce livestock losses and thus to reduce potential conflicts with wildlife.

O conflito entre humanos e carnívoros silvestres devido à predação exercida sobre rebanhos domésticos tem sido um dos precursores mundiais que tornam os carnívoros um dos grupos com espécies mais ameaçados de extinção. No Brasil, a predação por onças-pardas tem sido documentada em diversas regiões e como consequência a perseguição desses animais é fortemente observada. A fim de identificar os fatores que poderiam estar associados a predações aos rebanhos domésticos por onças-pardas no oeste do Estado de São Paulo, realizamos entrevistas com produtores rurais, utilizando questionários semi-estruturados, abordando características das propriedades, do manejo e da paisagem. Realizamos 71 entrevistas e identificamos propriedades que passaram por eventos de predação na última década. Ovinos e bovinos foram os grupos de animais mais frequentemente predados. Através da Regressão Logística foi possível obter um modelo de previsão de ataques com 81% de concordância entre estimado e observado, do qual o número de ovinos e a quantidade de vegetação natural presentes em cada propriedade foi positivamente relacionado aos casos de predação, porém o manejo das criações de risco como ovinos e bezerros pode contribuir significativamente para a redução de perdas de animais domésticos e assim reduzir possíveis conflitos com a fauna silvestre.
Puma attacking on domestic livestock in west of São Paulo State, Brazil
Keywords: Puma concolor; Predação; Gado; Regressão Logística; Manegment; Livestock; Predation